Technology Awareness of Artificial Intelligence (AI) Application for Public Procurement Process in Nigeria - Yamusa, M. A.; Lawal, H. S.; Abdullahi, M.; Ishaq, Z. H. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The public procurement process of acquiring goods, works and services has been observed to be suffering from inefficiencies in the forms of corruption cases, absence of transparency, faulty procedures, and dysfunctional bureaucratic ties. In Nigeria, it was discovered that the public procurement process has the potential of reaping the benefits of Artificial Intelligence (AI). However, the level of awareness of the public procurement practitioners of the significance of incorporating AI in procurement is yet to be studied. This study assessed the awareness of Artificial Intelligence application for public procurement processes in Nigeria. Data was collected using questionnaire survey. The questionnaire was distributed to public procurement practitioners with at least 5 years of experience in procurement. Data was analysed using Mean, Standard Deviation, and Relative importance index. Analysis of variance and Independent t-test was then used to ascertain the level of awareness of the respondents based on their attributes. The study discovered information about Artificial intelligence is quite vast as the parameter ‘I have heard about AI’ got the highest ranking with mean score of 3.63 and RII of 72.58%, while ‘I use AI for procurement processes’ to be the lowest ranking attribute with mean score of 1.50 and RII of 30.00% meaning even though information is available, the usage of AI for procurement is quite low. Additionally, the results show that while AI is a popular concept within procurement organisations, majority of the procurement practitioners have little knowledge of its application in public procurement. The research recommends that, public procurement organisations should develop the capacity of their employees on the utilisation of AI in procurement process.